2022
DOI: 10.1111/jcpt.13705
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin domain receptor 1 may be involved in biological barrier homeostasis

Abstract: What is known and objective: Discoidin domain receptor 1 (DDR1) is a receptor tyrosine kinase involved in the pathological processes of several diseases, such as keloid formation, renal fibrosis, atherosclerosis, tumours, and inflammatory processes. The biological barrier is the first line of defence against pathogens, and its disruption is closely related to diseases. In this review, we attempt to elucidate the relationship between DDR1 and the biological barrier, explore the potential biological value of DDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 124 publications
(279 reference statements)
0
1
0
Order By: Relevance
“…In addition to astrocytes, it also expresses among myelinating oligodendrocytes, myelin and neurons 80 . Ddr1 is important for the regulation of microglial activity 81 . It has been reported that Ddr1 mediates inflammatory response of microglia induced by collagen 82 , which may contribute to the neuroinflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to astrocytes, it also expresses among myelinating oligodendrocytes, myelin and neurons 80 . Ddr1 is important for the regulation of microglial activity 81 . It has been reported that Ddr1 mediates inflammatory response of microglia induced by collagen 82 , which may contribute to the neuroinflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%